Chemical Composition of Essential Oils from the Leaves, Seeds, Seed-pods and Stems of Bixa orellana L. (Bixaceae) - , Abdullatif O. Giwa-Ajeniya; , Abayomi Ademefun; , Oladipupo A. Lawal; , Isiaka A. Ogunwande (Archives of Current Research International, 2016)
Aims: The aim of the present study is to report the volatile compounds identified in the essential oils obtained by hydrodistillation from the various parts of B. orellana. Study Design: The design includes the extraction of essential oil from air-dried leaves, seeds, seed-pods and stems samples of B. orellana and the determination and identification of the chemical constituents of the oils. Place and Duration of Study: Mature leaves, seeds, seed-pods and stems of B. orellana were collected along LASU-Isheri Road in Alimosho Local Government Area, Lagos State, Nigeria, in May, 2014. Methodology: Air-dried and macerated leaves, seeds, seed-pods and stems of B. orellana were hydrodistilled in a Clevenger-type apparatus to obtained colourless volatile oil whose chemical constituents was analyzed by GC-FID and GC/MS. Results: A total of twenty-one different compounds were identified, out of which a range of 9–20 constituents were identified, accounting for 91.4–98.1% of the oil samples that are predominantly sesquiterpenes (40.8 – 94.9%), except for the seed oil with a higher amount of monoterpenes (45.0%). The leaf oil was characterized largely by α-guaiene (49.3%). The seed oil had α-pinene (29.1%) and β-pinene (14.5%). α-Guaiene (25.0%), spathulenol (12.0%) and caryophyllene oxide (9.7%) were the significant compounds of the seed-pot. The main constituents of the stem oil were caryophyllene oxide (38.8%), β-caryophyllene (22.3%) and myrtenyl acetate (12.5%). Conclusion: The present study shows that the composition of B. orellana essential oils differed from each other and from data reported previously from other parts of the world.